IN MY ART BODY IS BUDDY: Notes on social value of creative action; Notes on Role of Artist in quest of freedom - WILL, RALF G (IJRDO - Journal of Social Science and Humanities Research, 2019)
In my original body of work, a series of interviews, conducted between 1986 – 88, ART rises, strikes, and gains from RESISTANCE to racial segregation,  cultural exploitation, professional marginalisation. Independent references and sources corroborated my astonishing findings. Namely 1, the unravelling of abstraction, elitism and aloofness as false, if you like fake values, obstructing and confusing our appreciation of Art. Rather than deepening and opening up access to a seemingly all too often misunderstood yet inherently free practice, this socially-based act of artistic creation.